Physical morphometric characteristics and capacity curves of Abaya and Chamo Lakes - B. Awulachew, Seleshi (Zede Journal of Ethiopian Engineers and Architects, 2023)
The purpose of the study undertaken in this paper is aimed at investigating the Abaya and Chamo lakes, which are not previously studied in any meaningful detail regarding their water resources capacity. The paper discusses the bathymetry survey undertaken and the resulting morphomoteric characteristics derived as a result. The background lake map has been digitised and surveyed data has been also developed as digital values. The digital values have been interpolated and ·grids of the elevation surface have been generated From the digital values elevation area and elevation volume curves (capacity curves) of the two Lakes, which can describe the water resources capacity of the lakes body, have been developed Furthermore, immediate application of the result as a continuation of the study is highlighted in the paper